За прилошките определби за време во микенскиот грчки - Dzukeska, Elena (Филозофски факултет, Скопје, 2018)
Time expressions in Ancient Greek are versatile regarding their form, since the semantic role of Time in this language, like in other Indo-European languages is expressed with several different cases. The use of different cases is related to the conceptualization of Time. Although, there is no abundance of time expressions in the Mycenaean documents, the words for 'day', 'month', 'year' are attested and it has been observed that, just as in the Post-Mycenaean period, time expressions can be in genitive, dative-locative, accusative. In addition, on some of the tablets, when the date is specified with a month name, phrases that consist of forms that, cannot be easily explained as forms of the same case are used. The aim of this paper is to discuss and re-evaluate the meaning of the time expressions (consisting of nouns, nominal phrases or adverbs) found on the Linear B tablets, in terms of Time conceptualization. Furthermore, the evidence from the Mycenaean period is compared with relevant forms from the Post-Mycenaean period in order to deepen our understanding of the diachrony of the time expressions in the Greek language.
On time expressions in Mycenaean Greek
Keywords: time expressions, Mycenaean Greek, Semantic role